Tuan Guru Leadership Strategy in Implementing the Ma'had Curriculum: Multicase Study - Hadi, Samsul; Baharuddin, Baharuddin; Padil, Moh (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to analyze the leadership strategies of Tuan Guru in implementing the Ma’had curriculum in Ma’had Darul Qur’an Wal-Hadith Nahdlatul Wathan East Lombok and Ma’had Darul Hikmah Kediri West Lombok. This research uses a qualitative descriptive approach with a case study type and a multicase design. To obtain research data, researchers used observation, interviews and documentation methods. Checking the validity of the data using data triangulation and method triangulation. The research results show that first, the ma’had curriculum planning process includes planning objectives, content/teaching materials/materials, methods, media and evaluation by involving administrators, teachers and curriculum staff. This curriculum planning aims at transformative leadership and charismatic leadership. Second, the implementation of the ma’had curriculum includes learning methods (sorogan, bandongan and discussion methods), implementation of the contents/study materials of the yellow book (turats) and evaluation. The implementation of this curriculum combines the methods of the Salafi curriculum model and the integrated curriculum model which leads to a moderated curriculum model that strengthens the social reconstruction curriculum. And third, the implication of the Tuan Guru leadership strategy is to have graduates who master the yellow book and have a deep understanding of Islam, mahasantri become Islamic cadres and are able to contribute positively to Islamic educational institutions and society, mahasantri are able to apply Islamic teachings and become uswatun hasanah.